Modeling Smartphone Power - Alawnah, Sameer Allan (2013)
A Master of Science thesis in Computer Engineering by Sameer Allan Alawnah entitled, "Modeling Smartphone Power," submitted in June 2013. Thesis advisor is Dr. Assim Sagahyroon. Available are both soft and hard copies of the thesis.